Role of Biologics in Chronic Rhinosinusitis With Nasal Polyposis: State of the Art Review. (4th August 2020) - Kim, Christine; Han, Joseph; Wu, Tara; Bachert, Claus; Fokkens, Wytske; Hellings, Peter; Hopkins, Claire; Lee, Stella; Mullol, Joaquim; Lee, Jivianne T.
Abstract : Objective: To review the current literature regarding the role of biologics in the treatment of chronic rhinosinusitis with nasal polyposis (CRSwNP). Data Sources: PubMed/MEDLINE, EMBASE, Cochrane Review, ClinicalTrials.gov Review Methods: We conducted a comprehensive review of the literature on clinical studies investigating the efficacy of emerging biologics in CRSwNP, with a focus on randomized controlled trials. Conclusions: There appears to be promising evidence to support the safety and efficacy of biologics in CRSwNP with and without asthma for select patients. However, additional large‐scale randomized studies with longer follow‐up are necessary to determine which patients would benefit the most from these novel systemic treatments. Implications for Practice: Chronic rhinosinusitis with nasal polyposis refractory to medical and surgical therapy remains a challenging clinical problem for otolaryngologists. However, emerging biologic therapies may offer a new therapeutic option for such patients with recalcitrant disease.